Work-Education in the State-finance (Research, Society and Development, 2022)
The article aims to reflect some propositions of the State-finance dynamics based on the inseparable premise of the capitalist system: “Work-Education”. It is based, therefore, on the assumption that the State-finance is part of the historical and social development of the capitalist way of producing, being a product of human relations on nature. Thus, the contradictions of the financial system show dysfunctions in the socioeconomic process and, as a consequence, the effects of technological advancement and the setback of labor circumstances in globalized finance are mystified and the Human Capital Theory for education becomes the subsidy for the configuration of the modus operandi of interest-bearing capital through guidelines and directives from international organizations that are based on an entrepreneurial concept based on private solutions, within the scope of management and educational processes. That is why educational training based on socio-emotional skills aligns with the “new” onslaught of educational entrepreneurs, given that this is capable of resigning individuals to the conditions of increasingly flexible and precarious salaried work.